1980
DOI: 10.1159/000149200
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of Cell DNA in the Evaluation of Heteroploid Cells as Substrate for the Preparation of Killed Viral Vaccines

Abstract: To evaluate the risk of using heteroploid cell lines as substrates for viral vaccine production, the presence of cell DNA in poliovirus suspensions was examined. The time course of [3H]-thymidine-labeled HeLa cell DNA release during lytic infection with type 1 poliovirus was investigated. More DNA was found in filtered supernatants of poliovirus-inoculated cultures than in control cell supernatants. DNA concentration increased with time, paralleling virus release, but did not exceed 1.5% of the tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1982
1982
1986
1986

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…One of the main problems of epidemiological survey of poliomyelitis is to determine the vaccine or nonvaccine origin of poliovirus isolates (29). Several recently published papers have shown that some of the best methods for identification of the genetic origin of poliovirus isolates are oligonucleotide mapping of poliovirus RNA (14,21,23,30) and antigenic characterization by monoclonal antibodies (5,7,(10)(11)(12)24).…”
Section: Discussionmentioning
confidence: 99%
“…One of the main problems of epidemiological survey of poliomyelitis is to determine the vaccine or nonvaccine origin of poliovirus isolates (29). Several recently published papers have shown that some of the best methods for identification of the genetic origin of poliovirus isolates are oligonucleotide mapping of poliovirus RNA (14,21,23,30) and antigenic characterization by monoclonal antibodies (5,7,(10)(11)(12)24).…”
Section: Discussionmentioning
confidence: 99%